2019
DOI: 10.21203/rs.2.10745/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of Surgical site infections among patients undergoing open urological surgery at a Tertiary hospital, Tanzania: A cross sectional study

Abstract: Background Surgical site infection (SSI) is one of the major hospital acquired infections highly associated with prolonged hospitalization, morbidity and mortality. In open urological surgeries, little is known on magnitude and factors associated with development of SSI. Methods and Materials This was a cross-sectional prospective observational study performed between August 2015 and March 2016 at Muhimbili National hospital (MNH), Dar es Salaam, Tanzania. All patients who underwent open urological surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…7 Studies in Tanzania have reported high surgical site infection (SSI) rates ranging from 21.3% to 48.0% among patients undergoing surgery, including CS. [8][9][10][11][12][13] These rates are 5-18 times higher than rates in high-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…7 Studies in Tanzania have reported high surgical site infection (SSI) rates ranging from 21.3% to 48.0% among patients undergoing surgery, including CS. [8][9][10][11][12][13] These rates are 5-18 times higher than rates in high-income countries.…”
Section: Introductionmentioning
confidence: 99%